Evolution of Modified Glass Ionomer Cements: A Review - Susant Mohanty1 , Priyanka L. Kalimireddy2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Glass ionomer cement has been the subject of extensive research over the last few decades. Refinementswere made to the composition of GICs in an attempt to formulate an ideal restorative material (RM) havingstrength, adherence, natural appearance, and anticariogenicity. Contrary to early glass ionomers, the newrestorative systems are easy and practical to use. The emergence of GIC as a ‘material of choice’ for variousapplications in dentistry is mainly due to its fluoride-releasing and chemical bonding properties. This articlethrows light on the evolution and the course of recent advancements of Glass ionomer cement.